Achieving supply chain excellence through supplier management: A case study of fast moving consumer goods. Issue 9 (29th November 2018) - Salam, Mohammad Asif; Khan, Sami A.
Abstract : Purpose: The purpose of this paper is to develop a supplier selection and management program to improve overall supplier performance. Design/methodology/approach: Supplier performance is measured in terms of quality and delivery within a fast moving consumer goods (FMCG) business of a multinational company based in Thailand using a case study methodology. The quality and delivery related data were collected from daily deliveries at the manufacturing plant both before and after implementing the supplier management program. Findings: Findings of the study suggest that the selection of suppliers based on their performance is important for manufacturing firms. Moreover, the supplier selection and management program can contribute effectively to improving suppliers' performance. Research limitations/implications: This case study has been conducted based on a single company within the FMCG industry. Hence, it limits the generalizability of the findings across industries. Practical implications: The study provides a real-life tool for practitioners to learn about the importance of strategic decision-making process pertaining to the supplier selection and management program. Social implications: This study demonstrates that through a transparent supplier evaluation process, the firms can develop trust and long-term relationship with their suppliers for pursuing the goals of product development and innovation. Originality/value: Implementing a supplier management system is a critical step in enhancing an organization's overall competitiveness. To develop an effective supplier management system firms must have objective measures and share those with their suppliers. Developing metrics for suppliers' evaluation is the key to achieving continuous improvement as evidenced in this case.